Fixed point results for (ζ,η)-weakly cyclic generalized contraction mappings in b-metric spaces - Lemessa, Nigussa; Koyas, Kidane (Fixed point theory and algorithms for sciences and engineering, 2025)
The present study introduces ( ζ , η ) -weakly cyclic generalized contraction mappings in the context of b-metric spaces and investigates results of fixed-point for it. Our findings extend and generalize a large number of relevant fixed-point results from the current literature. Examples are provided to support the validity of our findings. Finally, we apply our findings to demonstrate the existence and uniqueness of a solution for a non-linear Fredholm integral equation.